963 Paediatric Full-Thickness Burns Caused by Cyanoacrylate Nail Adhesive - a Case Series. (19th August 2022) - Noton, T; Leon-Villapalos, J; Atkins, J
Abstract: Cyanoacrylate glue, often found in acrylic nail kits, reacts in an aggressive exothermic reaction with cotton fabric. These potentially dangerous adhesives are freely available and there remains little understanding about the consequences on contact with cotton. We present two paediatric cases of thermal burns related to the use of cyanoacrylate glue, both seen after the application of acrylic false nails. The first patient is a 14-year-old girl, who presented with a 0.25% TBSA full thickness burn to the left heel, after she spilt some of nail glue onto her sock. The burn wound was initially dressed in Flamazine, but later required a formal debridement and split thickness skin graft (SSG). The second patient is a 11-year-old girl, who presented with a 0.1% TBSA full thickness burn to the dorsal right foot, after applying false nails and again spilling the glue onto her sock. Immediate first aid with cold water was used. This patient was first managed in a local hospital before being referred to the burn's unit due to worsening pain. The wound was dressed in Acticoat, due to a sloughy appearance, and then underwent formal debridement and SSG. Cyanoacrylate burns are caused by a thermal reaction rather than chemical as most may believe. In both cases described, cotton is likely to have acted as a catalyst, which is consistent with published literature. Warnings on packaging to increase awareness of potential reactions should be mandatory, as well as childproof packaging to help deter the unsupervised use of such adhesives.